Anestesi Infus Gravimetrik Ketamin dan Propofol pada Anjing (THE GRAVIMETRIC INFUSION ANAESTHESIA WITH KETAMINE AND PROPOFOL IN DOGS) - Sudisma, I Gusti Ngurah; Widodo, Setyo; Sajuthi, Dondin; Soehartono, Harry (Jurnal Veteriner, 2013)
This study aim was to evaluate quality of anaesthesia by using gravimetric infusion anaesthesia withketamine and propofol in dogs. The quality of anaesthesia, duration of actions, and the physiological responsseof anaesthesia were evaluated in twenty domestic dogs. Anaesthesia was induced intramuscularly withatropine (0.03 mg/kg)-xylazine (2 mg/kg) (AX), intravenously ketamine-propofol (KP) (4 mg/kg), andmaintained with continuous intravenous infusion with pre-mixed propofol (P) and normal saline containing2 mg/ml of propofol and 2 mg/ml of ketamine (K). Domestic stray dogs were randomly divided into fivegroups. Groups AXKP-K2P2, AXKP-K4P4, and AXKP-K6P6 were treated with ketamine-propofol the dose0.2 mg/kg/minute, 0.4 and 0.6 mg/kg/minute respectively, while group AXKP-P4 was given propofol 0.4 mg/kg/minute and group AXKP-I was given isoflurane 1-2%. Heart rate (HR), respiratory rate (RR),electrocardiogram (ECG), blood oxygen saturation (SpO2), end tidal CO2 (ET CO2), and capillary refill time(CRT) were measured. No significant difference (P>0.05) found between the groups in anaesthetion times.All groups showed rapid and smooth inductions, prolonged surgical stage, and rapid recovery. Groups AXKPK2P2and AXKP-K4P4 showed minimal physiological effect on the dogs. The HR, RR, ET CO2, SpO2, CRT,and ECG wave were stabl. Combination of AXKP-K6P6 induced SpO2 depression, increased and instabilityof HR, RR and ET CO2. Groups AXKP-P4 showed decreased of HR and respiratory depression. All anaestheticcombinations showed no significant influence (P>0.05) on the electricity of the dog’s heart. The combinationof ketamine-propofol at dose 0.2 and 0.4 mg/kg/minute were found to be better as an application formaintaining anaesthesia by gravimetric continuous intravenous infusion. The method is a suitablealternative for inhalation anaesthesia in dogs.
Keywords: anaesthesia, gravimetric, ketamine, propofol, dogs